Uni-axial behaviour of expansive CFST and DSCFST stub columns. (15th June 2021) - Ho, J.C.M.; Ou, X.L.; Li, C.W.; Song, W.; Wang, Q.; Lai, M.H.
Highlights: Ten CFST and DSCFST columns with ordinary or expansive concrete were tested under uni-axial compression. Prestress of concrete in both axial and hoop directions was measured for specimens with expansive concrete. Use of expansive agent could improve the elastic modulus, yield and ultimate strengths of specimens. The yield and ultimate strengths of specimens were compared with current design codes. Abstract: Concrete-filled-steel-tube (CFST) and double-skinned concrete-filled-steel-tube (DSCFST) columns have superior strength, stiffness and ductility to that of traditional reinforced concrete columns. Despite the above merits, a major issue with these columns is that the steel-concrete interface bonding will be impaired by the concrete shrinkage and different lateral dilation of steel and concrete under compression. To mitigate the problem, the use of expansive concrete is proposed in this study. For verification, a total of 10 CFST and DSCFST stub columns containing ordinary or expansive concrete were fabricated and tested under uni-axial compression. The studying parameters are: (1) Replacement level of cement by expansive agent (0 or 20% by weight); (2) Steel tube dimensions; (3) Hollow section ratio of DSCFST columns. From the test results, some pre-loading confining stress was measured in both axial and hoop directions in specimens containing expansive concrete. It also revealed that using expansive agent could enhance the elastic modulus, yield and ultimate strengths of CFST and DSCFST columns. Lastly, the yield and ultimate strengths of these columns were compared with the design strength predicted by EC4, ACI and AISC, in which their applicability on CFST and DSCFST columns containing expansive concrete was investigated.